2020
DOI: 10.15561/20755279.2020.0208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of grip strength and somatotype features of armwrestling athletes of different skill levels

Abstract: Analysis of grip strength and somatotype features of armwrestling athletes of different skill levels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…A similar set of techniques was used in the study by Podrihalo et al [23] Comparison of the results of armwrestlers with different skill levels confirmed the importance of developing hand muscles and body structure for achieving success in this sport. The parallel study of handgrip in static and dynamic modes is important in armwrestling.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A similar set of techniques was used in the study by Podrihalo et al [23] Comparison of the results of armwrestlers with different skill levels confirmed the importance of developing hand muscles and body structure for achieving success in this sport. The parallel study of handgrip in static and dynamic modes is important in armwrestling.…”
Section: Discussionmentioning
confidence: 70%
“…In armwrestling, a strong and high-quality handgrip increases the likelihood of winning the fight. Podrihalo et al [23] assessed this indicator as one of the success predictors. The results of Podrigalo et al [24] confirmed the informativeness and significance of the strength index for assessing handgrip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Armwrestling refers to sports in which performance directly depends on strength readiness, particularly arm strength development. It was confirmed that the main predictions of success in hand wrestling include: muscle development, physical strength, the value of conditional moments of the strength of limb segments [18]. Strength fitness in many sports is used to assess athletes' physical fitness [5,11].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time in kicking martial arts these indicators are not very important and their absolute contribution in system formation is much lower” [ 16 ]. The strong grip is particularly important in such combat sports, such as judo, sambo, wrestling, and MMA [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%